Foreign policy of Elizabeth I - Pásztor, Renáta (Études sur la Région Méditerranéenne, 2023)
This study examines the foreign policy activities of Elizabeth I (1741–1761) and their implications for the Russian Empire. Despite being one of the least researched topics in historiography, Elizabeth I’s foreign policy holds significant importance, particularly in the context of the Russian Empire. Elizabeth’s foreign policy exhibited several key features and orientations. She pursued the doctrine of Peter the Great, specifically in securing and expanding Russian control over Baltic territories. The Empress’s foreign policy was influenced by her advisers, Jean Armand de Lestocq and Alexey Bestuzhev-Ryumin, and was characterized by a German orientation, primarily supporting Austria. Elizabeth actively participated in political coordination. In addition, the study explores the Empress’s role in the election of the Holy Roman Emperor and her efforts to maintain friendly relations with Prussia and Austria during the War of the Austrian Succession, as well as Russia’s participation in the Seven Years’ War.